Buddhism in Central Asia I Patronage, Legitimation, Sacred Space, and Pilgrimage - Meinert, Carmen; Sørensen, Henrik H. (Dynamics in the History of Religions, 2020)
Buddhism in Central Asia (Part I): Patronage, Legitimation, Sacred Space, and Pilgrimage, 6-14th Centuries deals with the various strategies of legitimation and the establishment of sacred space and pilgrimage among both trans-regional (Chinese, Indian, Tibetan) and local (Khotanese, Uyghur, Tangut, Kitan) Buddhist traditions. Readership: All interested in dynamics of inter-cultural encounter and Buddhist transfer in pre-modern Eastern Central Asia.